Endothelin-A Receptor Antagonist Alleviates Allergic Airway Inflammation via the Inhibition of ILC2 Function - Zhang, Xiaogang; Chen, Ziyang; Zuo, Shaowen; Sun, Hengbiao; Li, Xinyao; Lu, Xiao; Xing, Zhe; Chen, Meiqi; Liu, Jingping; Xiao, Gang; He, Yumei (Frontiers in Immunology, 2022)
Allergic airway inflammation is a universal airway disease that is driven by hyperresponsiveness to inhaled allergens. Group 2 innate lymphoid cells (ILC2s) produce copious amounts of type 2 cytokines, which lead to allergic airway inflammation. Here, we discovered that both peripheral blood of human and mouse lung ILC2s express the endothelin-A receptor (ETAR), and the expression level of ETAR was dramatically induced upon interleukin-33 (IL-33) treatment. Subsequently, both preventive and therapeutic effects of BQ123, an ETAR antagonist, on allergic airway inflammation were observed, which were associated with decreased proliferation and type 2 cytokine productions by ILC2s. Furthermore, ILC2s from BQ123 treatment were found to be functionally impaired in response to an interleukin (IL)-33 challenged. And BQ123 treatment also affected the phosphorylation level of the extracellular signal-regulated kinase (ERK), as well as the level of GATA binding protein 3 (GATA3) in activated ILC2s. Interestingly, after BQ123 treatment, both mouse and human ILC2s in vitro exhibited decreased function and downregulation of ERK signaling and GATA3 stability. These observations imply that ETAR is an important regulator of ILC2 function and may be involved in ILC2-driven pulmonary inflammation. Therefore, blocking ETAR may be a promising therapeutic strategy for allergic airway inflammation.